The Chinese Experience of Rapid Modernization: Sociocultural Changes, Psychological Consequences? - Sun, Jiahong; Ryder, Andrew G. (Frontiers in Psychology, 2016)
Mainland China has undergone profound changes dating back to the nineteenth century, including a contemporary period of rapid modernization that began in the 1980s. The result has been dramatic social, cultural, and economic shifts impacting the daily lives of Chinese people. In this paper, we explore the psychological implications of sociocultural transformation in China, emphasizing two central themes. First, rising individualism: findings from social and developmental psychology suggest that China’s rapid development has been accompanied by ever-increasing adherence to individualistic values. Second, rising rates of depression: findings from psychiatric epidemiology point to increasing prevalence of depression over this same time period, particularly in rural settings. We argue that links between sociocultural and psychological shifts in China can be usefully studied through a cultural psychology lens, emphasizing the mutual constitution of culture, mind, and brain. In particular, we note that the link between social change, individualism, and rising mental illness deserves careful attention. Our review suggests that shifting values and socialization practices shape emotion norms of concealment and display, with implications for depressive symptom presentation. The challenge comes with interpretation. Increasing prevalence rates of depression may indeed be a general response to the rapidity of sociocultural change, or a specific consequence of rising individualism—but may also result from increasingly ‘Western’ patterns of symptom presentation, or improvements in diagnostic practice. We conclude by considering the challenges posed to standard universal models of psychological phenomena.